PENERAPAN PSAP 13 PADA ASET TETAP PUSKESMAS X DALAM PROSES AUDIT OLEH KAP XY - Ramlah Ramlah; Rahmat Zuhdi (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to analyze the implementation of PSAP 13 on fixed assets at Puskesmas X during the audit process conducted by KAP XY. The study used a descriptive qualitative approach through field observation, document review, and analysis of audit working papers during the internship program at KAP XY. The focus of the study was directed toward the presentation, classification, depreciation, reconciliation, and disclosure of fixed assets in financial statements. The results indicate that fixed assets require special attention because they are material accounts related to accountability in public sector entities. The audit process emphasized physical inspection, reconciliation procedures, depreciation analysis, and disclosure evaluation. In addition, this study provides an understanding regarding the importance of orderly fixed asset administration in supporting fair financial statement presentation based on PSAP 13.